Framing Pemberitaan Rocky Gerung Dugaan Penghinaan Simbol Negara Di Media Kompas TV Dan CNN Indonesia - Risco Herlambang; Sumaina Duku; Jawasi (CV. ITTC INDONESIA, 2024)
The framing of Rocky Gerung's news as an alleged insult to state symbols in the media Kompas TV and CNN Indonesia. The research aims to determine the framing of Rocky Gerung's news regarding alleged insults to state symbols in the media Kompas TV and CNN Indonesia. Use of research: To increase insight into the analysis of news framing about Rocky Gerung, an insult to state symbols. This research uses a qualitative descriptive research method, which is a form of qualitative research that aims to reveal facts, circumstances, phenomena, variables and situations that occurred during the research, by providing a clear picture. -explained: The problems studied in qualitative descriptive research can refer to quantitative studies, comparative studies, and can even be correlational studies between one element and another element of a natural object. analysis of the Kompas.com and CNN Indonesia reports regarding the alleged insult to state symbols by Rocky Gerung, it was concluded that there were significant differences in the approach to news framing between the two media. Kompas.com places greater emphasis on legal and political aspects, focusing on the legal steps taken by the party who reported Rocky Gerung. Meanwhile, CNN Indonesia put forward Rocky Gerung's clarification, emphasizing that his criticism was aimed at government policy. It is important for people who use the media to be smarter in reading the news. News is a construction created by the editors of tvoenenews.com and CNN Indonesia. News should not include the opinions of the parties reporting, but should focus on facts that are relevant to the event or issue being reported. The media must also pay attention to the 5W+1H (Who, What, When, Where, Why, How) elements in preparing news.